Ultrastructure of the midgut epithelium of Meliponinae larvae with different developmental stages and diets - Serrao, J. E.; da Cruz-Landim, C. (Int Bee Research Assoc, 2000)
The comparative study of the ultrastructure of the midgut epithelium of stingless bee larvae that eat plant protein (pollen) and animal protein (carrion) throughout the larval phase, shows variations in the digestive cells that are only relative to larval aging and not to the type of larval diet. The cells of older larvae present a cytoplasm with empty spaces that result from emptying of lipid and glycogen stocks, and the presence of autophagic vacuoles. These results are discussed in relation to the hypothesis that variations in the digestive tract of insects may be associated with different diets or phylogeny. We conclude that different diets do not determine cell morphology adaptations in the studied species. As the variations in the ultrastructure of the midgut epithelium are the same in all studied species, including the necrophagous species Trigona hypogea, throughout the larval stage, this sequence of changes seems to be due to different physiological state during larval development.
Keywords: stingless bees; Meliponinae; larvae; midgut; development; digestive cells; diet; necrophagy; morphology